Plan estratégico de posicionamiento para la compañía Firma Global Consultores en la ciudad de Cali. - Alvarado Alvarez Lina Clareth (Universidad Antonio Nariño, 2024)
The focus of this research was oriented towards the approach of strategies for the positioning of the company FIRMA GLOBLAL CONSULTORES S.A.S. Knowing the work and development in their years of experience in the provision of accounting and tax services was important to identify the functionalities and particularities according to the real organizational structuring of the company.